Corporate Communication in Growing Internal Relations of Employees PT. Pupuk Indonesia Sales Department Region 1 North Sumatera - Nabila, Nadia Muthi; Zulkarnain , Iskandar; Kurniawati, Dewi (PT FORMOSA CENDEKIA GLOBAL, 2024)
his research aims to analyze how corporate communication activities foster internal relationships between employees of PT. This research uses a qualitative approach to describe the data findings and data analysis carried out. Researchers used data analysis using the Miles Huberman and Saldana method which includes data condensation, data display, and then drawing conclusions. The research results that researchers found that corporate communication was carried out by PT Pupuk Indonesia Sales Department Regional 1 using the employee relations stages, downward communication through direction and coordination carried out directly through meetings, and indirect communication through communication media such as WhatsApp and Zoom, as well as providing training, rewarding and motivational education programs to employees. The novelty found in this research as a differentiator from similar research that has been carried out previously is the use of corporate communication theory combined with employee relations theory to analyze phenomena that occur in the research object.